2020
DOI: 10.1080/15476286.2019.1708549
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer analysis of RNA methyltransferases identifies FTSJ3 as a potential regulator of breast cancer progression

Abstract: RNA methylation, catalysed by a set of RNA methyltransferases (RNMTs), modulates RNA structures, properties, and biological functions. RNMTs are increasingly documented to be dysregulated in various human diseases, particularly developmental disorders and cancer. However, the genomic and transcriptomic alterations of RNMTs, as well as their functional roles in human cancer, are limited. In this study, we utilized an unbiased approach to examine copy number alterations and mutation rates of 58 RNMTs in more tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 122 publications
2
31
0
Order By: Relevance
“…FTSJ2 (also known as MRM2) is a mitochondrial rRNA methyltransferase [52]. Human FTSJ3, which likely catalyzes 2'-O-Me of both rRNA and internal sites of mRNA, is a potential regulator of breast cancer progression [53]. Furthermore, FTSJ3 catalyzes 2'-O-Me of HIV RNAs and leads to the inhibition of innate immune sensing and response [45].…”
Section: Discussionmentioning
confidence: 99%
“…FTSJ2 (also known as MRM2) is a mitochondrial rRNA methyltransferase [52]. Human FTSJ3, which likely catalyzes 2'-O-Me of both rRNA and internal sites of mRNA, is a potential regulator of breast cancer progression [53]. Furthermore, FTSJ3 catalyzes 2'-O-Me of HIV RNAs and leads to the inhibition of innate immune sensing and response [45].…”
Section: Discussionmentioning
confidence: 99%
“…DNA hypomethylation has also been found to be associated with increased NSUN2 expression in breast cancer, and NSUN2 overexpression promoted cell proliferation, migration, and invasion while NSUN2 knockdown inhibited these processes in vitro and in vivo [ 97 ]. A more detailed pan-cancer analysis has determined that expression of several RNMTs, including NSUN2, had positive correlations between DNA copy number and mRNA expression and was associated with higher grade aggressive subtypes and poor prognosis in breast cancer patients [ 98 ]. While the initial studies of NSUN2 in breast cancer found no association with ER status or Ki67 [ 95 ], in contrast, the study by Yi et al found significant correlations with estrogen receptor, Ki-67, and the progesterone receptor [ 97 ].…”
Section: Known Roles For Nsun2 In Cancermentioning
confidence: 99%
“…Most recently, a pan-cancer analysis of RNMTs has shown that alterations to NSUN2 are common in lung cancer [ 98 ], although this was not followed up in more detail. In this regard, cBioPortal analysis [ 111 , 112 ] of the TCGA lung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LUSC) datasets indicates that alterations to NSUN2 were found in 37% and 44% of samples, respectively ( Figure 3 ).…”
Section: Known Roles For Nsun2 In Cancermentioning
confidence: 99%
“…The protein contains a putative RNA-methyltransferase domain (FtsJ) in the N-terminal region and two uncharacterized domains in the central (DUF3381) and C-terminal (Spb1_C) regions [95]. A recent study demonstrates a functional role of FTSJ3 in promoting BC growth and survival, therefore representing a novel putative target for anticancer treatment [96]. The essential gene RNA helicase A (DHX9) is a protein responsible to regulate transcription in an ATP-dependent manner and involved in chromatin remodeling identified by Tarallo et al [89].…”
Section: Interaction Proteomics As Tool For Estrogen Signaling Proteimentioning
confidence: 99%
“…The protein contains a putative RNA-methyltransferase domain (FtsJ) in the N-terminal region and two uncharacterized domains in the central (DUF3381) and Cterminal (Spb1_C) regions [95]. A recent study demonstrates a functional role of FTSJ3 in promoting BC growth and survival, therefore representing a novel putative target for anticancer treatment [96].…”
Section: Interaction Proteomics As Tool For Estrogen Signaling Proteimentioning
confidence: 99%